Swift J045558.9-702001, a new HMXB in the LMC - Vasilopoulos, G.; Sturm, R.; Haberl, F.; Maggi, P.; Udalski, A. (The Astronomer's Telegram, 2013)
We report a new high-mass X-ray binary (HMXB), found in a Swift observation performed on 2013 October 11 as part of the monitoring of the nova LMC2012 (ObsId: 00049549004). The Swift/XRT count rate was 0.023±0.008 cts s-1, corresponding to a flux of 1.6×10-12 erg cm-2 s-1 (0.3-10 keV) and an unabsorbed luminosity of 5.1×1035 erg s-1 for LMC distance (50 kpc).
Keywords: Binary; Neutron Star; X-Ray